Determinant Premature Rupture of Membrane - Ekayanti, Ekayanti; Ghita, Dwi; Marina, Marina (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2022)
Premature rupture of the membrane is a complication that threatens the soul of both the mother and the baby born. This article aims to determine the factors that can increase premature rupture of amniotic fluid so that prevention can be done. The study was conducted at the health centre for ten months. Research design with a case control study approach using the purposive sampling technique, collecting data using observation sheets. History of premature rupture of membrane, age, parity and employment status. This study used a research design with a case control study approach using a purposive sampling technique with a sample of 15 respondents who experienced prom and 15 respondents who did not experience prom collecting data using observation sheets. Results showed that of the 30 people who were used as samples, 16 mothers had a history, there were 13 (81.2%) cases of premature rupture of membranes. Based on the results of chi square analysis, the value of = 0.000 < from 0.05. Conclusion There is a relationship between the history of prom, age, and parity with prom's incidence advice for pregnant women to avoid risk factors that increase the incidence of amniotic rupture early.